The Effect of Renderforest Application-Based Learning Media and Teacher Creativity on Student Learning Motivation at St. John Catholic Elementary School 1 Tomohon - Jini Carolina Dien; Harol R. Lumapow; Aldjon N. Dapa (International Journal Labs, 2026)
This study aims to analyze the impact of Renderforest-based learning media and teacher creativity on student learning motivation at SD Katolik I St. Yohanes Tomohon. Motivated by the observed lack of student motivation, evidenced by low participation, initiative, and perseverance in completing tasks, this research explores how digital media and teacher creativity can enhance learning motivation. Using a quantitative approach with simple regression and multiple regression analysis, the study finds that Renderforest-based learning media has a strong positive influence on students' learning motivation, contributing 99.4%. This shows that Renderforest significantly enhances student interest, attention, participation, and enthusiasm during learning. Additionally, teacher creativity also proves to have a significant impact, contributing 97.2% to motivation. Teachers’ ability to design innovative lessons, effectively use media, create a positive learning environment, and adapt to students’ needs is crucial in boosting motivation. Furthermore, the combination of Renderforest media and teacher creativity together accounts for 99.4% of the variance in students’ motivation, indicating a significant contribution. The findings suggest that integrating innovative learning technology with teacher creativity is an effective strategy to enhance motivation in the digital era. This research emphasizes that both Renderforest-based learning media and teacher creativity are essential factors in increasing learning motivation at SD Katolik I St. Yohanes Tomohon.